Repair Strategies in Online Chat: A Conversation Analysis - Ari Tiara (Passage, 2018)
The study aims to: (1) investigate the types of repair strategies, (2) identify the techniques of repair initiation, and (3) discover the possible purposes of particular types of repair that are employed by the participants in a group chat namely Calterone 33. A group’s chat room which consists of 32 participants was chosen to explore the repair strategies. The dialogues contain repair were analysed by using Schegloff, Sacks, and Jefferson’s theory (1977) and Finegan’s theory (2008). The results of the present study reveal that the participants in Calterone 33 used all types of repair strategies in which other-initiated self-repair appears as the most frequently occurs (52.5%). It was affected by the topic selection from the participants with different knowledge which triggered the recipient to initiate a repair. Three techniques of repair from Finegan (2008) were found in group’s chat room, with an asking question technique as the most applied. It was used as the participants urge the explanation of the trouble source from the current speaker. Another technique was discovered in the chat, namely giving possible understanding. Repair strategies were used in online chat for some functions such as to get a further explanation, to clarify a thing, and to rectify the mistyping in the utterance. This study contradicts Zaferanieh (2004) and Meredith and Stokoe (2013) for its claim that SISR appears as the most applied in online chat; nevertheless, it supports Schonfeldt and Golato (2003), Sato (2012), Kendrick’s (2015) study about the use of SISR and other-initiation in conversation. Those findings indicate that the participants in Calterone 33 tend to initiate repair from others’ mistakes which affected by different understanding of the topic. They use other-initiation in order to get an explanation of the trouble source. Keywords: conversation analysis, repair strategy, online chat